Herbicide programs, cropping sequences, and tillage-types: a systems approach for managing Amaranthus palmeri in dicamba-resistant cotton - Vulchi, Rohith; Nolte, Scott; McGinty, Joshua; McKnight, Benjamin (Frontiers in Agronomy, 2023)
Herbicide-resistant Amaranthus palmeri poses a significant threat to cotton production in the US. Tillage, cover crops, crop rotations, and dicamba-based herbicide programs can individually provide effective control of A. palmeri, but there is a lack of research evaluating the above tactics in a system for its long-term management. Field trials were conducted near College Station and Thrall, TX (2019–2021) to evaluate the efficacy of dicamba-based herbicide programs under multiple cropping sequences and tillage types in a systems approach for A. palmeri control in dicamba-resistant cotton. The experimental design used was a split–split plot design. The main plots were no-till cover cropping, strip tillage, and conventional tillage. The subplots were cotton:cotton:cotton (CCC) and cotton:sorghum:cotton (CSC) sequences for 3 years within each tillage type, and sub-subplots were a weedy check (WC), a weed-free check (WF), a low-input program without residual herbicides (LI), and a high-input program with residual herbicides (HI). Using HI under the CSC sequence was the only system that provided >90% control of A. palmeri for 3 years across all tillage types and locations. By 2021, A. palmeri densities in the CSC sequence at College Station (4,156 plants ha−1) and Thrall (4,006 plants ha−1) are significantly low compared to the CCC sequence (31,364 and 9,867 plants ha−1, respectively) when averaged across other factors. Similarly, A. palmeri densities in HI at College Station (9,867 plants ha−1) and Thrall (1,016 plants ha−1) are significantly low compared to LI (25,653 and 13,365 plants ha−1, respectively) when averaged across other factors. We also observed that the CSC sequence reduced A. palmeri seed bank by at least 40% compared to the CCC sequence at both College Station and Thrall when averaged across other factors. Over 3 years, we did not observe significant differences between LI and HI for cotton yields at College Station (1,715–3,636 kg ha−1) and Thrall (1,569−1,989 kg ha−1). However, rotating cotton with sorghum during 2020 improved cotton yields by 39% under no-till cover cropping in 2021 at Thrall. These results indicate that using dicamba-based herbicide programs with residual herbicides and implementing crop rotations can effectively manage A. palmeri in terms of seasonal control, densities, and seed bank buildup across tillage types and environments.